2002
DOI: 10.1074/jbc.m203167200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-3-3ζ as a Protein Kinase B/Akt Substrate

Abstract: Protein kinase B/Akt (PKB/Akt) is a member of the ACG kinase family, which also includes protein kinase C, that phosphorylates a number of 14-3-3-binding proteins. 14-3-3 protein regulation of protein kinase C activity is modulated by 14-3-3 phosphorylation. We examined the hypothesis that PKB/Akt interacts with and phosphorylates 14-3-3, leading to modulation of dimerization. By glutathione S-transferase pull-down, Akt precipitated recombinant 14-3-3 and endogenous 14-3-3 from HEK293 cell lysates. Recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 23 publications
1
58
0
2
Order By: Relevance
“…Furthermore, the identification of 14-3-3 as an Aktbinding partner in CA1 SH immunoprecipitates was not entirely surprising. Akt substrates have been shown to associate with 14-3-3 in a phosphorylation-dependent manner, and we have demonstrated previously that 14-3-3 associates with Akt and is an Akt substrate (73). However, the role of 14-3-3 in the cellular response to SH and/or IH remains to be elucidated.…”
Section: Expression Of Constitutively Active Akt In Pc-12 Cells Inducmentioning
confidence: 95%
“…Furthermore, the identification of 14-3-3 as an Aktbinding partner in CA1 SH immunoprecipitates was not entirely surprising. Akt substrates have been shown to associate with 14-3-3 in a phosphorylation-dependent manner, and we have demonstrated previously that 14-3-3 associates with Akt and is an Akt substrate (73). However, the role of 14-3-3 in the cellular response to SH and/or IH remains to be elucidated.…”
Section: Expression Of Constitutively Active Akt In Pc-12 Cells Inducmentioning
confidence: 95%
“…Two additional point mutants of 14-3-3 isoforms have been well characterized; mutation of serine 58, known to be phosphorylated by PKA or PKB/AKT1, to alanine (S58A) induces constitutive dimerization of 14-3-3, whereas mutation of this serine to aspartic acid (S58E) abrogates dimerization (31)(32)(33). However, as shown in Fig.…”
Section: Interaction Between Gpsm3 and 14-3-3 Family Membersmentioning
confidence: 99%
“…1 Other targets of Akt include eNOS, caspase 9, Bad, 14−3−3 proteins, and p47 phox . 8,[19][20][21][22] Of these targets only Bad and FOXO were reported to be phosphorylated by Akt in mesangial cells. 7, 13 Recent work by Lewis et al using a proteomic approach to define targets of ERK phosphorylation suggested that a majority of substrates for specific kinases remain to be identified.…”
Section: Introductionmentioning
confidence: 99%